Some Reflections on the Fighting Power of the Italian Army in North Africa, 1940–1943. (November 2015) - Carrier, Richard
Most Anglo-American scholars neglect the contribution of the Italian army to the Axis campaign in North Africa, and depict most Italian combatants and units as weak and ineffective, prone to surrender. This paper proposes an analysis of the fighting power of Italian units during the campaign. It assesses how both weapons and training influenced the fighting power of men and units. Additionally, it suggests that two contingencies, the role of surprise and the presence of German troops, came into play. As a result, despite a growing technical stagnation in terms of weapons and equipment, most Italian units adapted, became efficient, and kept fighting mostly because of the emphasis put on training by numerous Italian officers.